2007
DOI: 10.3892/or.18.1.261
|View full text |Cite
|
Sign up to set email alerts
|

Expression of erbB-1 and erbB-2 genes in normal and pathological human endometrium

Abstract: Abstract. Overexpression of the erbB-1 (EGFR, epidermal growth factor receptor) and erbB-2 (HER2/neu) proteins contributes to the aggressive behavior of malignant tumors originating from the endometrium. We currently examined whether the trend of these proteins to overexpression is a direct effect of their gene transcriptional activities. Expression of the erbB-1/erbB-2 genes was measured applying the quantitative RT-PCR technique in 25 uterine carcinomas, 12 normal endometria, a carcinosarcoma and a case of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
0
14
1
Order By: Relevance
“…Also, the gene expression of HER2-neu shows significantly more expression in malignant than benign endometrium. 53 These data are contradictory to our results, yet our numbers are small. Furthermore, the results of HER2-neu expression should be interpreted with caution because only 8 samples (21%) stained positive.…”
Section: Discussioncontrasting
confidence: 95%
“…Also, the gene expression of HER2-neu shows significantly more expression in malignant than benign endometrium. 53 These data are contradictory to our results, yet our numbers are small. Furthermore, the results of HER2-neu expression should be interpreted with caution because only 8 samples (21%) stained positive.…”
Section: Discussioncontrasting
confidence: 95%
“…Abnormal activation may lead to cell excessive proliferation, malignant transformation and tumorigenesis. Clinical studies have shown that EGFR was overexpressed in 60∼80% endometrial carcinomas, especially in poor differentiation, advanced, recurrent, or metastatic endometrial cancer 14,15 . A study in vivo demonstrates that EGFR expression in type II EC Hec50co cell is higher than that in type I EC Ishikawa cell 16 .…”
Section: Discussionmentioning
confidence: 99%
“…EGFR overexpression is common in endometrial cancer and has been correlated with tumor grade, deep myometrial invasion, and poor prognosis 71 73 . The EGFR family consists of four distinct tyrosine kinase cell-surface receptors: ErbB-1 (EGFR), ErbB-2 (HER2/neu), ErbB-3, and ErbB-4.…”
Section: Molecular Targeted Therapiesmentioning
confidence: 99%